Chronic fluoxetine rescues changes in plasma membrane density of 5-HT1A autoreceptors and serotonin transporters in the olfactory bulbectomy rodent model of depression. (25th July 2017) - Riad, Mustapha; Kobert, Antonia; Descarries, Laurent; Boye, Sandra; Rompré, Pierre-Paul; Lacaille, Jean-Claude
Highlights: We used the olfactory bulbectomized rats as model of depression. The plasma membrane density of 5-HT1A auto-receptors in 5-HT neurons was increased in bulbectomized rats. The plasma membrane density of serotonin transporters in 5-HT neurons was increased in bulbectomized rats. These changes induced by bulbectomy were reversed by chronic fluoxetine treatment. Abstract: Reduced serotonin (5-HT) neurotransmission is postulated to underlie the pathogenesis of depression. The serotonin transporter (SERT) and 5-HT1A auto-receptors act in concert to ensure homeostasis of serotonin (5-HT) neurotransmission and regulation of their cell surface expression represent efficient mechanisms to maintain this homeostasis. Thus, we investigated the changes in the subcellular distribution of SERT and 5-HT1A receptors (5-HT1AR) in the rat olfactory bulbectomy model of depression using immuno-gold labeling and electron microscopy, and examined the effect of chronic treatment with the antidepressant, fluoxetine, a serotonin reuptake inhibitor, on the subcellular distribution of SERT and 5-HT1AR. The density of plasma membrane labeling of 5-HT1A auto-receptors on dendrites of dorsal raphe neurons was increased after bulbectomy, but the 5-HT1A hetero-receptor membrane labeling on dendrites of CA3 hippocampal neurons was not. The density of membrane labeling of SERTs was increased both in dendrites of dorsal raphe neuron and axon terminals in the hippocampus after bulbectomy. However, the proportion of 5-HT1AR and SERT membrane labeling relative to total labeling was unchanged, suggesting an increase in protein levels. The increases in 5-HT1AR and SERTs membrane labeling induced by bulbectomy were reversed by chronic fluoxetine treatment, and these changes were associated with a reduction in the relative proportion of membrane versus total labeling, consistent with a protein shift between subcellular compartments. Our findings support the hypothesis that changes in efficacy of serotonergic neurotransmission in this model of depression depends on both activity and density of cell surface-expressed SERT and 5-HT1A auto-receptors.